A MANFAAT PEMBERIAN JUS BUAH BIT PADA IBU HAMIL DENGAN ANEMIA TERHADAP PENINGKATAN KADAR HEMOGLOBIN DI WILAYAH KERJA PUSKESMAS KEC. JATINEGARA DAN PUSKESMAS KEC. KRAMAT JATI JAKARTA TIMUR TAHUN 2019 - irwanti Gustina (Ikatan Bidan Indonesia (IBI), 2020)
BENEFITS OF GIVING BIT FRUIT JUICE IN PREGNANT WOMEN WITH ANEMIA TO IMPROVING HEMOGLOBIN LEVELS Irwanti Gustina1, Mella Yuria R.A 2, Putri Sarah Dita3 * D3 Midwifery Study Program at Binawan University Email: iragustina80@gmail.com ABSTRACT Introduction: Anemia in pregnancy due to iron deficiency because an increase in blood volume results to be blood thinning so that hemoglobin levels decrease and anemia occurs. Beetroot are one type of food that is recommended for consumption by pregnant women with anemia because they contain zink and folic acid. Method: This research is a quasy experimental study with a non-equivalent control-group design. The study was conducted on 40 pregnant women with anemia which were the experimental group and the control group. Results: As many as 40 pregnant women respondents with anemia were in the second trimester of pregnancy (57.5%), the highest number of pregnancies (parity) were multipara (57.5%), the education level of the majority of respondents were at the high school level (57.5% ), and the level of knowledge of most respondents in the good category (85%). The significant conclusion between beetroot juice administration on the increase in Hemoglobin levels of pregnant women with p value less than 0,001. Discussion: with the relationship between drink beetroot juice and the increase in Hemoglobin levels for pregnant women, it is expected that the Primary Health Care will educate pregnant women about beetroot juice that can be consumed to increase Hemoglobin levels. Key Words; Anemia; Hemoglobin; Beetroot